The learning of two similar complex movement sequences: Does practice insulate a sequence from interference? - Panzer, S.; Shea, C. H. (Human Movement Science, 2008)
Researchers found evidence to indicate that the memory state(s) underpinning the production of a movement sequence that was practiced for one day was essentially "overwritten" when another similar sequence was subsequently practiced on the next day. An interference paradigm was used to determine if additional practice on the first sequence would insulate it from retroactive interference arising from learning a new similar sequence. Participants produced the sequences by moving a lever with their right arm/hand to sequentially presented target locations. The experimental group practiced one 16-element movement sequence (S1) for two consecutive days. A second 16-element sequence (S2) was practiced on Day 3. The sequence practiced on Day 3 was created by switching the positions of 2 of 16 elements in the sequence practiced on the first day. Control groups received either two days of practice on S1 or one day of practice on S2. Contrary to our earlier findings (Panzer, Wilde, & Shea, 2006) of strong retroactive interference when S1 was only practiced for one day, we found no evidence of retroactive interference when S1 was practiced for two days prior to the switch to S2 practice. Interestingly, but also contrary to our earlier findings, we found the learning of S2 was facilitated by the prior practice of S1. This proactive facilitation was observed in S2 acquisition and on the S2 retention test.